Gambaran Pengetahuan Kehilangan Gigi Pada Lansia - Muh. Amrin Utama Lubis; Nurul Safira Maulida; Zilal Islamy Maramma; Ainun Ayu Yuniar (Jurnal Terapi Gigi dan Mulut, 2025)
Tooth loss is a condition in which one or more teeth are detached from their sockets or places, usually caused by disease in the periodontal tissues. The WHO defines that at least elderly individuals should have at least 20 functioning teeth, which indicates that their chewing ability is close to normal, although it may be slightly reduced. This study aims to determine the knowledge of the elderly at RSGMP Hasanuddin University regarding tooth loss. The type of research used is descriptive research method with a survey research design. The sample in this study consists of all elderly individuals receiving treatment at RSGMP Hasanuddin University in the prosthodontics department from July 15, 2025, to August 2025, totaling 20 people. The sampling technique used is total sampling with a sample size of 20 respondents, and the data is analyzed using SPSS with bivariate analysis (cross-tabulation). Based on the research results at RSGMP Hasanuddin University, the majority of respondents are aged 65 years (30%), and most of them are female (85%), with the dominant profession being housewives (75%). The respondents' knowledge about tooth loss varies, with 45% having good knowledge, 40% having moderate knowledge, and 15% having poor knowledge, with females tending to be more knowledgeable than males. The phenomenon of tooth loss also increases with age, especially among housewives, who account for 75% of the total respondents experiencing tooth loss. These findings indicate the need for improved awareness and knowledge about dental health in the community.